THE DEVELOPMENT OF LESSON PLAN FOR TUTORING CLASSES: ENGLISH COURSE - Vitara, Natalia (Jurnal Ilmiah Spectral, 2021)
A lesson plan is an important component that the teacher must prepare before carrying out learning activities. This study aims to develop lesson plans, especially tutoring for informal institutions. This research is an R&D research. The limitation of this research is that it is only carried out at the ADD stage (Analysis, Design, and Development). At the analysis stage, the teacher did not yet have a lesson plan, so the implementation of learning was not directed and only helped students in doing homework they got from school. At the design stage, the lesson plan components followed Brown’s (2001) theory which consisted of goals, objectives, materials and equipment, procedures, evaluations, extra-class work (if students needed them, to learn more at home). The development stage determined the appropriate method to be used in the learning process. At this stage, the lesson plans were validated by experts in the field of education to measure product quality.